Recent Advances on Designs and Applications of Hydrogel Adhesives - Liu, Xiaowei; Yu, Haojie; Wang, Li; Huang, Zhikun; Haq, Fazal; Teng, Lisong; Jin, Meijin; Ding, Binbin (Advanced materials interfaces, 2022)
In virtue of extracellular features, hydrogels have been used in various areas such as tissue repair, artificial skins, and biological electronics, etc. Intact contact of tough hydrogels to targeted surfaces is usually required to avoid blood or body fluids leakage or inaccurate signals of sensors. The collaboration of high interactive energy between interfaces and high fracture toughness of the constituent hydrogels can effectively prevent relatively macroscopic motions of adhesives from substrates under deformation. Nevertheless, variations in surface microenvironment like moisture, roughness, and functional groups can lead to the scission of bonds between bulk hydrogel and surfaces. Accordingly, to prevent detachment of adhesives, specific tactics should be utilized to reach a targeted surface based on substrates’ physical and chemical properties. This review concentrates on various hydrogel adhesives in the near‐decade, from design strategies, including physical interactions, chemical bonds, and bio‐inspired ways, to eventual applications, like wound closure, sensors, soft robots, and tissue repair. Meanwhile, it is anticipated that these approaches could spur sparks for fabricating appropriate tough adhesives under different circumstances. The state‐of‐art hydrogel adhesives spanning from design principles, including physical and chemical interactions and bio‐inspired strategies to eventual applications in soft robots, tissue repair, and wound closure and sensors are summarized.